[PP.14.23] J CURVE PHENOMENON. AN ANALYSIS OF BLOOD PRESSURE AND CARDIOVASCULAR EVENTS IN HYPERTENSIVE PATIENTS WITH CORONARY ARTERY DISEASE AND IMPAIRED SYSTOLIC FUNCTION. (September 2017) - Kallistratos, M.; Giannitsi, S.; Vasilopoulou, E.; Poulimenos, L.E.; Iliou, K.; Koukouzeli, A.; Kouremenos, N.; Chamodraka, E.F.; Skyrlas, A.; Kontogiannis, N.; Pagoni, S.; Daskalaki, A.; et al.
Abstract : Objective: Low blood pressure is associated with worse outcome in hypertensive patients with coronary heart disease. A J curve phenomenon has been reported between blood pressure and cardiovascular events in those patients. The purpose of the study was to determine the relationship between on-treatment BP and cardiovascular outcomes (death or heart transplantation) in hypertensive patients with CAD and impaired left ventricle systolic function. Design and method: We prospectively followed-up 77 hypertensive patients with coronary heart disease and impaired left ventricular function for 28.1 ± 9.9 months. During this period, 15 patients died and 2 underwent heart transplantation. Blood samples for NT-proBNP assessment were taken at baseline and before cardiopulmonary exercise to estimate peak oxygen consumption (VO2). LV cavity diameter, left atrial size and LV ejection fraction were measured by echocardiography. Results: Patients with systolic BP levels < 117 mmHg presented increased NT pro BNP plasma levels (2280 ± 2075 vs 947 ± 877, p = 0.001) at baseline in confront to patients with BP > 117 mmHg, worse peak VO2 levels (13.8 ± 3.9 vs 18.2 ± 4.6, p < 0.0001) and increased VEVC02 slope (41.2 ± 9.1 vs 35.5 ± 7.3, p < 0.01) respectively. In addition, patients with systolic BP < 117 mmHg, were on worse NYHA class (2.4 ± 0.6 vs 1.9 ± 0.8, p < 0.05) and presented decreased inotropic and chronotropic response to exercise (peak SBP at exercise 134.8 mmHg ± 27.6 vs 170.4 ± 24.5 mmHg, p < 0.001) and (peak HR at exercise 123.4 ± 17 bpm vs 137 ± 24 bpm, p < 0.05) respectively. Finally, patients with systolic BP <117 mmHg presented 3 fold increase odds ratio for death or heart transplantation (p < 0.05). Conclusions: Systolic blood pressure levels < 117 are associated with worse clinical condition and worse outcome. More studies with larger sample are needed in order to verify a J curve phenomenon between blood pressure and cardiovascular events in hypertensive patients, with CAD and impaired systolic function.